2008
DOI: 10.1042/cs20080050
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and diabetes: lipids, ‘nowhere to run to'

Abstract: Although specific pathogenic entities contributing to diabetic risk, such as central adiposity, ectopic fat accumulation, hyperlipidaemia and inflammation, are well-characterized, the response of cellular systems to such insults are less well understood. This short review highlights the effect of increasing fat mass on ectopic fat accumulation, the role of triacylglycerols (triglycerides) in Type 2 diabetes mellitus and cardiovascular disease pathogenesis, and selected current therapeutic strategies used to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 121 publications
3
33
0
Order By: Relevance
“…Type 2 diabetes, in particular, is a metabolic disorder characterized by high blood glucose levels that result from defects in insulin action (Hill et al, 2009). It is caused by the non-responsiveness of body cells to insulin rather than by defective insulin production (Fadini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes, in particular, is a metabolic disorder characterized by high blood glucose levels that result from defects in insulin action (Hill et al, 2009). It is caused by the non-responsiveness of body cells to insulin rather than by defective insulin production (Fadini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is strongly associated with different illnesses such as type 2 diabetes and cardiovascular diseases (14,23). Increasing prevalence of obesity has been proposed to be a consequence of both increased energy availability and reduced energy expenditure superimposed on a genetic background evolved for survival in conditions of food deprivation (30).…”
Section: Introductionmentioning
confidence: 99%
“…[31]. It is now widely recognized that a high calorie western food diet contributes greatly to the development of metabolic syndrome [32,33]. Recent literature suggested that diets with high content of fat and simple carbohydrate, especially fructose, are strongly associated with insulin resistance [34][35][36].…”
Section: A High Fat Diet Modelmentioning
confidence: 99%